The moderating effect of alexithymia on the relationship between stress and cyberchondria - Zhou, Yi; Dai, Lisha; Deng, Yunlong; Zeng, Hongling; Yang, Lifeng (Frontiers in Psychiatry, 2022)
The aim of this study is to investigate the moderating effect of alexithymic on the relationship between stress and cyberchondria. The research was carried out on a total 1117 students in college. According to the results, the Pearson correlation showed Cyberchondria has a significant positive correlation with stress and alexithymia. Furthermore, the regression analysis described that stress and alexithymia were the significant positive predictors of cyberchondria. Moreover, moderation analysis showed that Alexithymic significantly strengthened the association between Stress and cyberchondria. The study will help medical practitioners to understand how stress and alexithymia can cause an increase in cyberchondria. This will help them to elaborate operational indications for prevention and psychological support.